(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2026)
The balance between the development of tourism and the conservation of biodiversity is an issue of great concern to those nature-based places, such as the UNESCO Global Geoparks, among them. The study examines governance concerns associated with protecting sea turtles at the Belitong UNESCO Global Geopark, Indonesia, in the context of wildlife tourism. The qualitative part of the research has been informed by a policy analysis, site visits, literature review, and secondary data from tourism activities and conservation management on Belitung Island. The analysis is underpinned by a socio-ecological systems perspective that promotes the understanding of the interplay between ecological resources, human practices, and governance systems in a complex system. Moreover, while some wildlife tourism practices seem to contribute positively to the economic development in tourism (for instance, the release of sea turtle hatchlings for tourists to participate), these practices, when not closely supervised by scientific bodies, can be ecologically hazardous. Moreover, without unified and integrated administrative governance of tourism, conservation, and regional development, opportunities may be missed for governance voids that can contradict conservation imperatives. The findings are especially relevant for geopark governance and scientific conservation practice, as they address both the coordination of institutions and practices of science-based management of geopark governance. It would be anticipated that the improved levels of community participation and responsible wildlife tourism protocols make it more likely that tourism development in the Belitong UNESCO Global Geopark supports not only biodiversity conservation, but also regional sustainable development.